What is Attractive to Intention Job Seeker? - Fien Zulfikarijah; Muhammad Raja Khwarizmi (Universitas Muhammadiyah Malang, 2023)
Purpose – This study aims to investigate which factors employers should focus on in their job seeker strategies. The present study tested the respondent perception and analyzed relationships between social media, brand corporate, and career choice about intentions to apply for a job. Design/methodology/approach – Electronic questionnaires were distributed to students at higher education institutions in Malang. The proposed model is analyzed based on 136 responses related to two well-known Indonesian firms, they are BUMN and Government. Findings – The results indicate that several employer attributes are positive for social media, brand corporate reputation, and career choice to intention job seeker, which again is related to the attraction of potential employees. Specifically, social media is the strongest predictor of intention to apply for a job. The research is original in the way it combines social media, brand corporate, and career choice, which will be valuable to employers in their recruitment processes.